Scale of Good Practices in Food Handling Services: Instrument for the evaluation of the hygienic and sanitary safety of food by handlers (Research, Society and Development, 2023)
This research sought to evaluate the presence of good food handling practices, based on current Brazilian legislation. This is a descriptive, cross-sectional study, approved by the Research Ethics Committee, carried out with food handlers participating in a training course on good handling practices, where sociodemographic data were collected and the Good Practices Scale was applied in Food Handling Services in order to collect information regarding the practices of these food handlers regarding the hygienic and sanitary control of food. 68 food handlers participated, the majority of whom were female (86.8%) and had incomplete higher education (35.3%). Among the participants, 84% presented a “satisfactory” classification, followed by 13% with a “needs improvement” classification regarding the practice and sanitary hygiene control of food based on the general score of the scale, with the Temperature Control and Guidance Materials domains being those that require greater attention among those surveyed, respectively 35% of classification needs improvement/insufficient and 16% non-existent, with the Personal Hygiene domain being the best classified where 88% presented satisfactory results. Due to the lack of Brazilian instruments to measure the practice of food handlers regarding care during handling, the Scale of Good Practices in Food Handling Services emerges as a promising instrument, where critical points can be identified and based on them corrective measures can be implemented, with continued training being an effective and extremely important tool in this process.